2009
DOI: 10.1159/000209358
|View full text |Cite
|
Sign up to set email alerts
|

Free PSA/Total PSA Ratio Increases the Detection Rate of Prostate Cancer in Twelve-Core Biopsy

Abstract: Background: In the present study, we compared 12- with 8-core biopsy in patients with prostate-specific antigen (PSA) levels of 4.0–20.0 ng/ml. We also examined whether the free/total (F/T) PSA ratio is useful for cancer detection in 12-core biopsy. Methods: A total of 419 men with PSA level between 4.0 and 20.0 ng/ml underwent transrectal ultrasound-guided transperineal needle biopsies of the prostate. Of these men, 235 underwent 8-core biopsy and 184 underwent 12-core biopsy. We compared the cancer detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
5
1
Order By: Relevance
“…Another study also in Japan by S. Egawa et al in 2002 showed that the probalities of prostate cancer at percent free PSA values of <10.0, >10 15, >15-20, >20-26 and >26 were 58.3, 40.8, 25.3, 14.3 and 7.6% respectively when analysed without regard to findings on palpation when the total PSA value was between 41-10.0ngm/ml. 10,11,12 In our present study we found very high total PSA value in Prostate cancer patients but the free PSA level was not statistically significant as found in this study. Yet in another study in Finland by Finne P et al in 2002 showed that prostate cancer probability depended most strongly on the percentage of free PSA, total PSA, prostatic volume and DRE also contributed to prostate cancer probability, whereas age and family history of prostate cancer did not.…”
Section: Methodscontrasting
confidence: 57%
“…Another study also in Japan by S. Egawa et al in 2002 showed that the probalities of prostate cancer at percent free PSA values of <10.0, >10 15, >15-20, >20-26 and >26 were 58.3, 40.8, 25.3, 14.3 and 7.6% respectively when analysed without regard to findings on palpation when the total PSA value was between 41-10.0ngm/ml. 10,11,12 In our present study we found very high total PSA value in Prostate cancer patients but the free PSA level was not statistically significant as found in this study. Yet in another study in Finland by Finne P et al in 2002 showed that prostate cancer probability depended most strongly on the percentage of free PSA, total PSA, prostatic volume and DRE also contributed to prostate cancer probability, whereas age and family history of prostate cancer did not.…”
Section: Methodscontrasting
confidence: 57%
“…Early‐stage prostate cancer detection is vital to ensuring effective, curative treatment, and more patients are now undergoing prostatectomy, external radiation therapy, brachytherapy and active surveillance. Several reports have evaluated PSA and the free/total (F/T) PSA ratio, which have been proposed to detect this cancer at an early stage [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It can normally increase up to 6.5 ng/ml in men aged 70-79 years. [31,32] Prostate specific antigen and prostate cancer progression When PSA was first identified in SF and later on in serum, it was thought to be wholly specific to the prostate and differentially expressed in normal, benign, and malignant prostate tissues. [20,21] It therefore became widely used for screening, diagnosis, and therapeutic monitoring of prostate diseases.…”
Section: The Pitfalls Of Prostate Specific Antigen Testingmentioning
confidence: 99%
“…Other novel test methods for PSA that could be amenable to point of care testing include electrochemical detection, optical biosensing, and mass sensitive detection. [31] Unfortunately, the detection limits of these newer methods are not yet comparable to those of ELISAs. The availability of commercial anti-PSA antibodies and pure PSA antigens is also facilitating the progress in the development of other forms of immunometric assays.…”
Section: The Analytical Strength Of Prostate Specific Antigen Testingmentioning
confidence: 99%